Picture-based insurance (PBI): Smartphone pictures for affordable crop insurance - Ceballos, Francisco (2019)
Presented by Francisco Ceballos, Associate Research Fellow, IFPRI, at the International Microinsurance Conference, Lusaka, November 8, 2018.